Pendekatan Andragogi dalam Pembinaan Karakter Religius Muallaf Dewasa di Pusat Pembangunan Tamadun Masyarakat Asli (PETAMA) Pahang Malaysia - Muhamad Zikri; Reno Andika; Ifnie Yulfa (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to examine the application of the andragogical approach in the religious character development of adult converts at the Centre for the Development of Indigenous Civilisation (PETAMA) in Pahang, Malaysia. This study employs a qualitative approach, utilising data collection techniques such as observation, interviews and documentation. The data were analysed using thematic analysis through the stages of data reduction, theme grouping, and drawing conclusions to identify patterns of andragogical application in the development process. The results of the analysis indicate that the andragogical approach was applied in a structured manner, positioning participants as active subjects in experience-based learning. Key findings reveal three significant patterns: participatory learning, the integration of religious material with participants’ life experiences, and the role of the facilitator in emphasising spiritual guidance. The impact of this application is evident in the increased religious understanding, changes in religious attitudes and behaviour, and the growth of independence and self-confidence among adult converts. Thus, the andragogical approach has proven effective in supporting the development of religious character in a more meaningful and sustainable manner.